Trends of Islamic Religion Education in Higher Education: A Bibliometric Review - Siti Zulaikhah; A. Gani; Zaki Faddad Syarif Zain (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2025)
This study aims to map and analyze the research trends related to Islamic religious education in higher education over the last five years. The study was conducted through a literature review using a bibliometric approach on 87 articles taken from Scopus and SINTA databases, with 35 selected articles that met the inclusion criteria from 2020 to 2025. The selection and data analysis process followed the PRISMA protocol to ensure the validity and quality of the findings, while bibliometric visualization was carried out using VOSviewer 1.6.20 software. The findings show that 2021 became the peak of publication activity, primarily focusing on the professional development of Islamic Religious Education teachers and the digitalization of Islamic learning among students. In addition, the issue of inclusive religious education and interfaith dialogue also received attention as a response to efforts in reducing radicalism and strengthening cross-religious understanding. The network co-occurrence analysis revealed significant attention to the impact of the pandemic on the effectiveness of Islamic Religious Education learning. Most of the studies (84%) used a qualitative approach, showing a strong tendency of researchers to examine the implementation of Islamic values deeply, especially in integrating spirituality, character strengthening, and the formation of ethical behavior of students in higher education.